Gut microbiota–derived short-chain fatty acids and kidney diseases - Li L; Ma L; Fu P (Dove Medical Press, 2017)
Lingzhi Li, Liang Ma, Ping Fu Kidney Research Institute, Department of Nephrology, West China Hospital of Sichuan University, Chengdu 610041, China Abstract: Gut microbiota and its metabolites play pivotal roles in host physiology and pathology. Short-chain fatty acids (SCFAs), as a group of metabolites, exert positive regulatory effects on energy metabolism, hormone secretion, immune inflammation, hypertension, and cancer. The functions of SCFAs are related to their activation of transmembrane G protein-coupled receptors and their inhibition of histone acetylation. Though controversial, growing evidence suggests that SCFAs, which regulate inflammation, oxidative stress, and fibrosis, have been involved in kidney disease through the activation of the gut–kidney axis; however, the molecular relationship among gut microbiota–derived metabolites, signaling pathways, and kidney disease remains to be elucidated. This review will provide an overview of the physiology and functions of SCFAs in kidney disease. Keywords: gut microbiome, short-chain fatty acids, kidney diseases, gut–kidney axis